2020
DOI: 10.3390/nano10020207
|View full text |Cite
|
Sign up to set email alerts
|

A Tunable Triple-Band Near-Infrared Metamaterial Absorber Based on Au Nano-Cuboids Array

Abstract: In this article, we present a design for a triple-band tunable metamaterial absorber with an Au nano-cuboids array, and undertake numerical research about its optical properties and local electromagnetic field enhancement. The proposed structure is investigated by the finite-difference time domain (FDTD) method, and we find that it has triple-band tunable perfect absorption peaks in the near infrared band (1000–2500 nm). We investigate some of structure parameters that influence the fields of surface plasmons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(45 citation statements)
references
References 69 publications
1
44
0
Order By: Relevance
“…In Figure 3a,b, it can be seen that the two observed absorption peaks essentially originate from the fundamental and second order graphene SPP resonances, respectively. In addition, it can also be seen that the electric fields near the interface area between the graphene and PDMS substrate are composed of propagating waves related to the far-field interaction and evanescent waves, which correspond to the near-field interaction effect [50][51][52]. In summary, it can be concluded that the stronger electric field confinement characteristics of the unit cell structure above are consistent with the absorbance spectra shown in Figure 2a.…”
Section: Resultssupporting
confidence: 78%
“…In Figure 3a,b, it can be seen that the two observed absorption peaks essentially originate from the fundamental and second order graphene SPP resonances, respectively. In addition, it can also be seen that the electric fields near the interface area between the graphene and PDMS substrate are composed of propagating waves related to the far-field interaction and evanescent waves, which correspond to the near-field interaction effect [50][51][52]. In summary, it can be concluded that the stronger electric field confinement characteristics of the unit cell structure above are consistent with the absorbance spectra shown in Figure 2a.…”
Section: Resultssupporting
confidence: 78%
“…The excitation of surface plasmons resonance will produce oscillating dipole elds due to the semicircle nanostructure with small diameters relative to the incident wavelength of the different CP lights [43][44][45][46]. When RCP or LCP light excites the semicircle nanostructure, a chiral-selective absorption and giant CD effect will occur, and the electric eld and magnetic eld components of each layer are different due to the chirality [46][47][48][49][50][51]. charges are separated and mainly accumulated at the corners of the each semicircle nanostructure, acting like an electric dipole.…”
Section: Resultsmentioning
confidence: 99%
“…That is to say, the larger the imaginary part of permittivity is, the greater the loss of light is. However, noble metals just can arouse very narrow absorption peaks owing to its small imaginary part of permittivity [34]. On the contrary, refractory metals can cause higher light absorption within broadband because of its large imaginary part of permittivity [35][36][37].…”
Section: Introductionmentioning
confidence: 99%